Financial literacy and its determinants: The case of rural smallholder farmers in Indonesia - Retnoningsih, Dwi; H. Chung, Rebecca (Journal of Tropical Rural Development, 2025)
This study reveals the determinants of financial literacy of rural smallholder farmers in Indonesia with using the IV-Probit methodology based on primary cross-sectional data. The results show that these farmers are generally low in their financial literacy, and it is shaped by other factors such as socio-economic and farm operational characteristics. Participation in farmers' groups is considered the most critical of all the factors influencing financial literacy, followed closely by income. Other positive determinants include exposure to radio, altitude of farm location, education, access to capital and financial services, and farming experience, but effects seem to be at relatively smaller magnitudes. The results indicate the necessity for direct interventions, such as developing community-based groups with the participation of financial institutions and government representatives, and using mainstream media, particularly radio, to disseminate financial information and education. Enhanced financial literacy among smallholder farmers will enable them to make informed financial choices, thus promoting economic welfare and poverty alleviation in line with Sustainable Development Goals 1 (No Poverty) and 8 (Decent Work and Economic Growth).